DISTRIBUTION OF INSOLUBLE POLYSACCHARIDES IN THE ANTHERS OF GUAIACUM OFFICINALE L. DURING MICROSPOROGENESIS – AN ENDANGERED PLANT. - CHAITRA B. NEGALUR; H.C.LAKSHMAN (International Journal of Pharma and Bio Sciences, 2016)
Distributions of insoluble polysaccharides have been examined, during microsporogenesis of Guaiacum officinale L. The results revealed that polysaccharides appeared in the tissues of anther clearly demonstrated the role of biochemical substances during the formation of pollen grains. The results confirmed the anthers of Guaiacum officinale L. at early and late sporogenous tissue and tapetum lack polysaccharides. However, the anther wall layer showed the basic type of wall development and deposition of polysaccharide in the cytoplasm. The storage starch grains appear in the connective tissue. The anther wall layer at early meiotic stage the storage persists but in connective varies. Since the cytokinesis is simultaneous type resulting in the formation of tetrahedral tetrads. At the tetrad stage, the tapetum synthesis storage starch. When microspores are released from the tetrad the starch storage in the wall layers reappeared. The variable amounts of insoluble polysaccharides have been seen in the 2-celled pollen grains. The wall of the pollen grains is tricalporate. The mature pollen is engorged with plentiful of starch grains. However, as the anther matures, the starch storage decreases gradually and this suggests it’s utility as an energy source for the process of meiosis and pollen development.